Assessment of the Concentration of Transforming Growth Factor Beta 1-3 in Degenerated Intervertebral Discs of the Lumbosacral Region of the Spine - Staszkiewicz, Rafał; Gładysz, Dorian; Sobański, Dawid; Bolechała, Filip; Golec, Edward; Sobańska, Małgorzata; Strojny, Damian; Turek, Artur; Grabarek, Beniamin Oskar (Current issues in molecular biology, 2024)
The purpose of this study was to evaluate the feasibility of using the expression profile of transforming growth factor beta (TGF-β-1-3) to assess the progression of L/S spine degenerative disease. The study group consisted of 113 lumbosacral (L/S) intervertebral disc (IVD) degenerative disease patients from whom IVDs were collected during a microdiscectomy, whereas the control group consisted of 81 participants from whom IVDs were collected during a forensic autopsy or organ harvesting. Hematoxylin and eosin staining was performed to exclude degenerative changes in the IVDs collected from the control group. The molecular analysis consisted of reverse-transcription real-time quantitative polymerase chain reaction (RT-qPCR), an enzyme-linked immunosorbent assay (ELISA), Western blotting, and an immunohistochemical analysis (IHC). In degenerated IVDs, we noted an overexpression of all TGF-β-1-3 mRNA isoforms with the largest changes observed for TGF-β3 isoforms (fold change (FC) = 19.52 ± 2.87) and the smallest for TGF-β2 (FC = 2.26 ± 0.16). Changes in the transcriptional activity of TGF-β-1-3 were statistically significant (p < 0.05). Significantly higher concentrations of TGF-β1 (2797 ± 132 pg/mL vs. 276 ± 19 pg/mL; p < 0.05), TGF-β2 (1918 ± 176 pg/mL vs. 159 ± 17 pg/mL; p < 0.05), and TGF-β3 (2573 ± 102 pg/mL vs. 152 ± 11 pg/mL) were observed in degenerative IVDs compared with the control samples. Determining the concentration profiles of TGF-β1-3 appears to be a promising monitoring tool for the progression of degenerative disease as well as for evaluating its treatment or developing new treatment strategies with molecular targets.